2019
DOI: 10.1039/c9ta02935d
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm of ultrathin 2D nanomaterial adsorbents in aqueous media: graphene and GO, MoS2, MXenes, and 2D MOFs

Abstract: Due to the high surface area, atomic-level thickness, and abundant exposed active sites, 2D nanomaterials are regarded potential high-performance adsorbents. We review four representative nanomaterials, graphene, MoS2, MXenes, and MOFs, for this application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 182 publications
0
41
0
1
Order By: Relevance
“…There are numerous published reviews in the fields of MXenes for energy, catalysis, and environmental remediation [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the reviews on the mechanical properties of self-standing MXenes are not yet reported [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous published reviews in the fields of MXenes for energy, catalysis, and environmental remediation [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the reviews on the mechanical properties of self-standing MXenes are not yet reported [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The removal of EPs by CWs is mainly through the absorption and degradation (Li, Gao, et al, 2019; Li, Li, et al, 2019; Li, Zhang, Zeng, et al, 2019; Li, Liu, Zhang, Li, et al, 2019; Li, Zhang, Xia, Wang, et al, 2019; Li, Zhang, Hu, et al, 2019; Li, Sun, Zhang, Feng, et al, 2019; Li, Wang, et al, 2019; Li, Yuan, Gao, et al, 2019; Rabello et al, 2019). Adsorption is an important way to remove EPs, and the substrate, soil, and sediment of packed bed in CWs play major roles in adsorption (Nguyen, Chao, & Chen, 2019; Nguyen, Afzal, et al, 2019; Sardana, Cottrell, Soulsby, & Aziz, 2019; Zhao, Yan, et al, 2019; Zhao, Jian, et al, 2019). The degradation of EPs in CWs is mainly through microbial degradation, photolysis, and hydrolysis (Tara et al, 2019).…”
Section: Engineered Wetlands and Natural Systemsmentioning
confidence: 99%
“…CAMs mainly include activated carbon (AC), carbon nanotubes (CNs), graphene, biochar (Kumari, Alam, et al, 2019; Kumari, Tyagi, et al, 2019; Wang, Ying, et al, 2019; Wang, Su, et al, 2019; Wang, Wang, et al, 2019; Wang, Huang, et al, 2019; Wang, Cai, et al, 2019; Wang, Zhu, et al, 2019; Wang, Yin, et al, 2019; Wang, Qian, et al, 2019; Wang, Zhang, et al, 2019; Yaashikaa, Senthil Kumara, Varjani, & Saravanan, 2019). Some properties, including specific surface area, pore structure, and surface functional groups, have significant impacts on the adsorption capacity of CAMs (Xing et al, 2019; Zhang, Liu, et al, 2019; Zhang, He, et al, 2019; Zhang, An, et al, 2019; Zhang, Cao, et al, 2019; Zhao, Yan, et al, 2019; Zhao, Jian, et al, 2019). In this way, many researchers focus on the modification of CAMs to improve their adsorption performance (Rasheed, Adeel, Nabeel, Bilal, & Iqbal, 2019; Zhang, Liu, et al, 2019; Zhang, He, et al, 2019; Zhang, An, et al, 2019; Zhang, Cao, et al, 2019).…”
Section: Physical and Physicochemical Separation Coagulation And Somentioning
confidence: 99%
“…[15][16][17][18] Carbon based nanomaterials are of considerable interests in sample preparation techniques, including graphene, graphene oxide and carbon nanotubes. [19][20][21][22] Graphene oxide (GO), a single or few-layer thick twodimensional carbon material derived from the chemical oxidation of graphite, shows excellent mechanical strength with high chemical stability. The large specic surface area and the presence of surface functional groups like epoxy (-COC-), hydroxyl (-OH), carboxyl (-COOH) and carbonyl (-C]O) at the edges and basal plane promotes the GO for its application in analytical science.…”
Section: Introductionmentioning
confidence: 99%